Inside Back Cover: The Nature of Activated Non‐classical Hydrogen Bonds: A Case Study on Acetylcholinesterase–Ligand Complexes (Chem. Eur. J. 8/2016). Issue 8 (13th January 2016) - Berg, Lotta; Mishra, Brijesh Kumar; Andersson, C. David; Ekström, Fredrik; Linusson, Anna
Abstract : The nature of non‐classical hydrogen bonds of the CH⋅⋅⋅Y type involving electron‐deficient CH donors has been investigated. The hydrogen bonds between the enzyme acetylcholinesterase and different drug‐like ligands were computationally analysed in their original protein milieu. The results show that the CH⋅⋅⋅O and CH⋅⋅⋅arene interactions activated by a proximal cation are dispersion dominated and comparable to or greater in strength than classical hydrogen bonds. More information can be found in the Full Paper by A. Linusson et al. onpage 2672 ff.